2019
DOI: 10.1111/jpn.13128
|View full text |Cite
|
Sign up to set email alerts
|

Effects of yeast culture supplementation and the ratio of non‐structural carbohydrate to fat on growth performance, carcass traits and the fatty acid profile of the longissimus dorsi muscle in lambs

Abstract: The effects of yeast culture (YC) supplementation and the dietary ratio of non‐structural carbohydrate to fat (NSCFR) on growth performance, carcass traits and fatty acid profile of the longissimus dorsi (LD) muscle in lambs were determined in a 2 × 3 full factorial experiment. Thirty‐six Small‐tailed Han lambs were randomly divided into six groups with six replicates per group. The lambs were fed one of the six pelleted total mixed rations (TMRs) for 60 days after 15 adaption days. The six rations were formed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…Similarly, Milewski and Zaleska (2011) reported a higher composition of cis -9, trans -11-CLA, C14:1, C18:2, and C22:6 fatty acids in the intramuscular fat of lambs supplemented with yeast. To corroborate these findings, Liu et al. (2019) investigated the efficacy of yeast on modifying the fatty acid profile in lambs and the results obtained revealed that yeast supplementation caused an increase in the concentration of linoleic acid in the muscle by reducing its conversion to stearic acid.…”
Section: Growth Performance and Quality Of Ruminant Products Following Yeast Treatmentmentioning
confidence: 94%
See 1 more Smart Citation
“…Similarly, Milewski and Zaleska (2011) reported a higher composition of cis -9, trans -11-CLA, C14:1, C18:2, and C22:6 fatty acids in the intramuscular fat of lambs supplemented with yeast. To corroborate these findings, Liu et al. (2019) investigated the efficacy of yeast on modifying the fatty acid profile in lambs and the results obtained revealed that yeast supplementation caused an increase in the concentration of linoleic acid in the muscle by reducing its conversion to stearic acid.…”
Section: Growth Performance and Quality Of Ruminant Products Following Yeast Treatmentmentioning
confidence: 94%
“…(2002) Crossbred young bulls (Zebu × European) F:C was 44:56 15 g of yeast per animal per day Increased linolenic acid concentration in the meat; increased n6:n3 ratio in meat Maggioni et al. (2009) Small-tailed Han lambs Pelleted total mixed rations 0.8 and 2.3 g of yeast/kg dietary dry matter An increased concentration of linoleic acid concentration in the muscle; a decreased conversion of linoleic acid to stearic acid Liu et al. (2019) Iranian Zandi lambs Forage and concentrate 3 and 4.5 g of yeast per lamb per day Increased meat fat; no effects on meat fatty acid composition Raghebian et al.…”
Section: Growth Performance and Quality Of Ruminant Products Following Yeast Treatmentmentioning
confidence: 99%
“…One of the common feed additives used by farmers and researchers is yeast culture (YC) ( 3 ), which is a natural product produced from yeast fermentation. YC contains, in addition to live and dead yeast cells, culture media and the products of metabolism, including proteins, polysaccharides (mainly β-glucans and mannan-oligosaccharides), lipids, vitamins, peptides, amino acids, nucleotides, organic acids, and antioxidants ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…YC contains, in addition to live and dead yeast cells, culture media and the products of metabolism, including proteins, polysaccharides (mainly β-glucans and mannan-oligosaccharides), lipids, vitamins, peptides, amino acids, nucleotides, organic acids, and antioxidants ( 4 ). YC supplementation has a range of beneficial effects, including increased feed intake ( 5 ), stabilisation of rumen pH ( 6 , 7 ), increased feed digestion ( 8 ), enhancement of overall immunity ( 9 , 10 ), and consequently improved animal performance ( 3 , 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…The changes induced by supplementing the feed with high levels of non-fibrous carbohydrates alter the rumen dynamics by reducing the pH, which can compromise the lipolytic processes in the rumen, interfering with the synthesis of fatty acids performed by microorganisms (Liu et al, 2019). As a result, the SFA content of the longissimus dorsi muscle of sheep increases, as described by Liu et al (2019).…”
Section: Discussionmentioning
confidence: 99%